ANALISIS FAKTOR PRODUKSI USAHATANI SEMANGKA DI KOTA DENPASAR(STUDI KASUS DI SUBAK INTARAN BARAT, DESA SANUR) - Malur, Karolus Lionkadya; Kardi, Cening; Pratiwi, Luh Putu Kirana (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
The study aimed to analyze the financing and benefits of analyzing production factors for watermelon production in Subak Intaran Barat, Sanur Village, Denpasar City. The study was conducted by purposive sampling in the location of Subak Intaran Barat, South Denpasar. Determination of samples using simplerandom sampling as many as 31 people. The analytical method areused income analysis and multiple linear regression with cobbdouglass measurements. Based on the results of the analysis, the average costs incurred for an average of 101.6 total (TC) of Rp.14,795,000, and the farming benefits obtained by farmers on watermelon farming were Rp.19,278,200 and R / C Average 2.30 so it's feasible for farming. For the average area of ​​100 are, the costs incurred Rp.14,562,007, and the profit is Rp.18,937,593. The results on factors of production decreases back to scale. The magnitude of the total coefficient value towards the regression from input is 0.921. This explains that the value of return to scale on watermelon farming in Subak Intaran Barat achieves decresing return to scale where every use is twice of organic fertilizer, insecticide, urea, and labor, then production will decrease less than twice. Production factors that can significantly increase watermelon production are seeds, functionides and ponska. This happens because the seeds used by farmers are superior seeds, besides the use of functionides is very effective in killing pests that can interfere with watermelon growth, while ponska helps in vegetative formation in watermelon because it is given at the beginning of plant growth.